KETIKA MASA DEPAN MENANTI : STUDI TENTANG EFIKASI DIRI MAHASISWA TINGKAT AKHIR DI PULAU JAWA - Waruwu, Imelda Enerstine; Gunawan, William (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The transition to the workforce demands that final-year students possess sufficient self-confidence in career decision-making, given the current high level of economic uncertainty and educated unemployment. This study focuses on mapping the Career Decision-Making Self-Efficacy (CDMSE) levels of final-year students in Java as an indicator of work readiness. Using a descriptive quantitative approach, this study involved 540 respondents selected using a cluster quota sampling technique with a valid and reliable CDMSE Short-Form instrument. The data analysis results indicate that the majority of students fall into the moderate to high self-efficacy category, with goal selection and planning being the most dominant aspects. Conversely, the occupational information gathering dimension was recorded as the lowest aspect, indicating a lack of literacy and in-depth exploration of the job market. It can be concluded that although students generally possess strong self-confidence in planning their future, there is an urgency for educational institutions to provide specific support to improve access to and exploration of career information so that graduates are better prepared to face the realities of the professional world. ABSTRAK Transisi menuju dunia kerja menuntut mahasiswa tingkat akhir memiliki keyakinan diri yang memadai dalam pengambilan keputusan karier, mengingat tingginya tantangan ketidakpastian ekonomi dan angka pengangguran terdidik saat ini. Penelitian ini berfokus untuk memetakan tingkat Career Decision-Making Self-Efficacy (CDMSE) mahasiswa tingkat akhir di Pulau Jawa sebagai indikator kesiapan kerja. Melalui pendekatan kuantitatif deskriptif, penelitian ini melibatkan 540 responden yang dipilih menggunakan teknik cluster quota sampling dengan instrumen CDMSE Short-Form yang valid dan reliabel. Hasil analisis data menunjukkan bahwa mayoritas mahasiswa berada pada kategori efikasi diri sedang hingga tinggi, di mana dimensi pemilihan tujuan (goal selection) dan perencanaan (planning) menjadi aspek yang paling dominan. Sebaliknya, dimensi pengumpulan informasi pekerjaan (occupational information) tercatat sebagai aspek terendah, mengindikasikan masih kurangnya literasi dan eksplorasi mendalam mengenai pasar kerja. Dapat disimpulkan bahwa meskipun secara umum mahasiswa memiliki kepercayaan diri yang kuat dalam merancang masa depan, terdapat urgensi bagi institusi pendidikan untuk memberikan dukungan spesifik pada peningkatan akses dan kemampuan eksplorasi informasi karier agar lulusan lebih siap menghadapi realitas dunia profesional.